Experimental and theoretical electron density of intermediates in palladium‐phenanthroline catalyzed carbonylation of amines and reductive carbonylation of nitroarenes. Issue 10 (21st November 2017) - Macchi, Piero; Ragaini, Fabio; Casati, Nicola; Krawczuk, Anna; Sironi, Angelo
Abstract : The accurate electron density distribution in Pd(Neoc)Cl2 (CO) (Neoc = 2, 9‐dimethyl‐1, 10‐phenanthroline) was measured and calculated to investigate the chemical bonding features, the electrostatic forces and the polarizable bonds in this complex, which is a prototype of the proposed intermediate in the catalytic carbonylation of amines and nitroarenes. The quantum theory of atoms in molecules enables to investigate the nature of the elusive fifth coordination in the complex, which is approximately intermediate between a bypiramid penta‐coordination and a square planar tetra‐coordination. The analysis of the electrostatic potential and of the distributed atomic polarizabilities enables to address the sites that are more prompt to react, in particular in the context of the catalytic cycle. © 2017 Wiley Periodicals, Inc. Abstract : Palladium‐phenanthroline (Pd‐Phen) complexes are active catalysts for important processes, like the nitroarene or the amine carbonylation. An elusive intermediate carbonyl complex plays a key role and its stereo‐electronic properties are here investigated through experimental and theoretical electron density analysis.